Verification mechanism for lightweight componenent-based environment based on IoC container - Leszko, Rafal; Pietak, Kamil (Computer Science, 2013)
The paper presents a concept of component verification framework dedicated to a particular lightweight component environment. A starting point of the paper constitutes a discussion about significance of verification process of syntax inconsistencies in the software development. Next, the need of verification in service-oriented and component-based systems are presented and various approaches of verification in existing component environments are explained. The main part of the paper introduces a concept of a functional integrity of component-based systems that utilize verification mechanisms checking components consistency. The proposed solution is built on fine-grained component environment (close to classes similarly to the Spring Framework) realized in AgE platform. Selected technical aspects of the framework design illustrate the considerations of the paper.